Pemberdayaan Masyarakat Mandiri Sosial Ekonomi Melalui Program Ketahanan Pangan di Desa Krueng Mate, Aceh Utara - Nugrahawati, Anis; Izwar, Akmal; Hakim, Syahirman; Muktitama, Asih Makarti; Rinaldi, Rinaldi; Azhar, Rossy; Irfannur, Irfannur (LPPM Umuslim, 2025)
This community service program aimed to empower residents of Krueng Mate Village, North Aceh, through yard-based local food security initiatives. The main issues identified were the underutilization of home yards and limited access to sustainable food sources. The program involved awareness sessions, technical horticultural training, seed distribution, planting, and growth monitoring. A participatory approach encouraged active community involvement. Results showed a plant survival rate above 85% and increased public knowledge and skills in managing yard crops. The program helped meet household food needs, reduce daily expenses, and strengthen community solidarity. The success of this initiative in Krueng Mate indicates that food security based on community empowerment can be an effective strategy to enhance socio-economic resilience. This activity is expected to be replicable in other villages to support sustainable development through local resource optimization.